(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Kadir S, Badaruddin, Nurlina, Ridwan I, Rianawaty F. 2016. The recovery of Tabunio Watershed through enrichment planting using ecologically and economically valuable species in South Kalimantan, Indonesia. Biodiversitas 17: 140-147. Watershed is a medium system where hydrological-biophysical processes as part of hydrological cycle and social, economic, and cultural events as the results of human intervention on natural resource occur. The increasing human population results in the increasing need of water that may reduce the availability of water, causing environmental degradation. The objectives of this study were to study the characteristics of Tabunio watershed and to give recommendation on the enrichment planting for the watershed recovery. This study used watershed ecological area approach and the data were analyzed spatially using GIS. The results showed that based on the characteristics of its components, Tabunio Watershed was categorized as moderately to very highly qualified for recovery. The recovery should be done through:(i)Â enrichment planting based on the land capability, land suitability and the legal function of the area, (ii) conservation of soil and water using vegetative and civil engineering methods, and (iii)Â issuance of regulations to increase the watershedâ€™s carrying capacity.